HARNESSING PENSION SYSTEM RESTRUCTURING FOR CAPITAL MARKET GROWTH: THE NEW STRATEGY FOR INCLUSIVE PROSPERITY - Azadov Og’abek Erkinjon o’g’li (Bright Mind Publishing, 2025)
Global demographic shifts, rising longevity, and strained public budgets are putting immense pressure on traditional pension systems. At the same time, many countries—particularly emerging markets and developing economies (EMDEs)—struggle with Unmet capital potential markets, leading to poorly managed savings allocation and limited financial inclusion. In this context, this article highlights a potentially transformative solution: the implementation of fully capitalized, privately held, community-managed, compulsory or reward-based pension (FPCCR) schemes. This article unpacks the thesis - both theoretical and empirical - for how pension scheme modernization FPCCR schemes can stimulate stock market development, optimize household savings behavior, and support stable economic growth.
Keywords: Pension reform, FPCCR (fully capitalized, privately held, community-managed, compulsory or reward-based), stock market development, financial inclusion, long-term capital, household savings, equity financing, intertemporal optimization, capital market, inclusive growth.